Menggali Motivasi Sosial dan Akademik di Balik Pemilihan Bahasa Arab oleh Lulusan Sekolah Menengah Atas - Yul, Widiya; Putri Saleha, Gena; Andrian, Riko; Abdurrahman Husein, Abdul Hakim; Ulya, Aqil Sajidil (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study explores the motivations of high school alumni in choosing the Arabic Language Education program at IAIN Kerinci, as well as the factors influencing their decision to select this major. A qualitative method with a descriptive analysis approach was employed. The findings reveal that students from non-boarding school backgrounds select the Arabic Language major for three main reasons: (a) religious motives, where they study Arabic to understand and teach Islamic teachings (fahm al-maqru); (b) academic motives, where they aim to comprehend Arabic sciences and skills (istima’, kalam, qira’ah, and kitabah); and (c) professional, practical, and pragmatic motives, such as becoming a teacher and communicating orally (muhadatsah) in Arabic. This research presents a novelty by refuting Herdah (2020) findings, showing that not all Arabic learners study the language for ideological and economic reasons. These insights offer a new perspective on the diverse motivations behind studying Arabic, providing a comprehensive understanding of their motivations.